2008
DOI: 10.1038/npp.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

A PET Study of Tiagabine Treatment Implicates Ventral Medial Prefrontal Cortex in Generalized Social Anxiety Disorder

Abstract: Corticolimbic circuitry has been implicated in generalized social anxiety disorder (gSAD) by several neuroimaging symptom provocation studies. However, there are limited data regarding resting state or treatment effects on regional cerebral metabolic rate of glucose uptake (rCMRglu). Given evidence for anxiolytic effects conferred by tiagabine, a g-aminobutyric acid (GABA) reuptake inhibitor, the present [ Following tiagabine treatment, vmPFC rCMRglu increased significantly in the gSAD group. Further, the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 47 publications
4
29
0
4
Order By: Relevance
“…One study reported greater orbitofrontal cortex activation to angry vs neutral prosody (Quadflieg et al, 2008). In contrast, other studies have found decreased activation (Van Ameringen et al, 2004) and decreased glucose metabolic rates in the ventromedial prefrontal cortex (Evans et al, 2009), which increased following treatment with tiagabine (Evans et al, 2009). Glutamate/creatine and NAA/creatine ratios appear to be elevated in the rACC and are correlated with symptom severity .…”
Section: Social Phobiamentioning
confidence: 83%
“…One study reported greater orbitofrontal cortex activation to angry vs neutral prosody (Quadflieg et al, 2008). In contrast, other studies have found decreased activation (Van Ameringen et al, 2004) and decreased glucose metabolic rates in the ventromedial prefrontal cortex (Evans et al, 2009), which increased following treatment with tiagabine (Evans et al, 2009). Glutamate/creatine and NAA/creatine ratios appear to be elevated in the rACC and are correlated with symptom severity .…”
Section: Social Phobiamentioning
confidence: 83%
“…Na maior parte dos estudos, foram utilizadas amostras clínicas 18,19,[27][28][29][30][31][32][33] ou amostras provenientes da população geral 23,[34][35][36][37][38][39][40][41] , e em quatro estudos 9,42-44 foram incluídas amostras mistas. Os demais estudos 20,[45][46][47][48][49][50] não descreveram a procedência da amostra utilizada.…”
Section: Resultsunclassified
“…Cinco estudos utilizaram também exames de neuroimagem como parâmetro de comparação, quatro optaram pela tomografia por emissão de pósitrons (PET) 19,27,45,47 e um, por tomografia computadorizada por emissão de fóton único (SPECT) 18 . A duração dos diferentes ensaios clínicos variou de 1 (N = 1) a 28 semanas (N = 1), tendo a maioria duração de 12 semanas (N = 8).…”
Section: Resultsunclassified
See 2 more Smart Citations